NILAI KEPEDULIAN SOSIAL SISWA SEKOLAH DASAR - Ade Juli Saraswati; Dhi Bramasta; Karma Iswasta Eka (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Purwokerto, 2020)
Pay attention to current conditions the current value of student care shows symptoms that are increasingly declining. This descriptive qualitative study aims to determine the process of instilling the value of low class students' social care and the forms of low class student social care values in elementary schools. Data collection by observation, interview and documentation. The results showed that the process of instilling the value of social care of low grade students was carried out through: 1) Integration in the personal development program in the form of routine school activities, spontaneous activities, exemplary, and conditioning; 2) Integration in subjects by inserting social care character values into syllabus and lesson plans, including social care character values in the learning process; 3) Integration in school culture in the form of integration in the classroom, school and non-school activities. Forms of social care values of low grade students include 1) Sharing food with friends; 2) Thanking people for help; 3) Mutual lending of peer learning equipment; 4) Collecting funds and goods that are still useful for victims of natural disasters.